Applying the lexicographic maximum solution of min-product fuzzy relational inequalities for finding the optimal pricing with a fixed priority in a supply chain system - Yan-Kuen Wu; Ching Feng Weng; Yuan Teng Hsu; Wang, Ming Xian (Iranian journal of fuzzy systems (Online), 2024)
Fuzzy relational inequalities composed by the min-product operation are established to model the optimal pricing with fixed priority in a single product supply chain system. The solution algorithm has been proposed for solving such an optimization problem and finding the optimal solution (is called lexicographic maximum solution). In this study, a novel approach is proposed to finding the optimal pricing with fixed priority in a single product supply chain system. This approach is based on new properties of solution set in a min-product fuzzy relational inequality. These new properties allow us directly determine the optimal value of variable without many duplicate checks in the solution procedure. A numerical example is provided to illustrate the procedure.